Avaliação da viabilidade econômica de sistemas fotovoltaicos para microgeração distribuída em propriedades rurais considerando diferentes linhas de financiamento - Toscan, Alysson Francisco (2022)
This work aimed at an economic feasibility study through comparative analysis between economic indicators, such as simple paybacks, discounted, Net Present Value (NPV), Internal Rate of Return (IRR) and Profitability Index (IL), which were calculated using the dimensioning of the existing photovoltaic system, taking into account financing lines from three banking institutions. The work was carried out on a rural property in the Western Region of the State of Paraná. The data were obtained from Companhia Paranaense de Eletricidade – COPEL, surveying the property's monthly energy consumption over a period of 12 months. The costs related to the implementation of the existing photovoltaic system, acquisition value of modules, inverters, cover supports, cabling and maintenance were considered. With this information and the data provided by the Frequency Inverter software, which provided the amount of energy generated by the system, simple paybacks, discounted and other economic indices were calculated, comparing the financial return between the financing lines presented, being that the banking institution “A”, for presenting the lowest interest rate, obtained the best results considering the economic indices discussed.